Aerodynamic Analysis of a Three-Bladed Pivoted Savonius Wind Turbine: Wind Tunnel Testing and Numerical Simulation - M. Amiri; M. Kahrom; A. R. Teymourtash (Journal of Applied Fluid Mechanics, 2019)
In this study, a three-bladed pivoted vertical axis Savonius wind turbine is subjected to numerical and experimental studies. The experiments are carried out in a subsonic open-jet type wind tunnel, where the instantaneous position of the opening/closing blades are also determined via high speed imaging. The effects of adding end plates and the rotor aspect ratio on the turbine torque and power coefficients are investigated experimentally. Results show that adding end plates greatly enhances the rotor aerodynamic performance, in terms of both the maximum power coefficient and also the working range of the turbine. Similar effects are also observed for the effects of increasing the aspect ratio. Comparing numerical results with the experimental data demonstrated that the numerical results are in a convincing agreement with the experimental data of a wind rotor with an aspect ratio of 2.0 equipped with end plates. Although there are several two-dimensional numerical simulations for the drag-based vertical axis wind turbines in the literature, the results of the current study suggests that two-dimensional numerical results are not comparable with the experimental data of the rotors with small aspect ratios, especially without end plates.